Oxaliplatin induced laryngospasm: a case series - George, Ancy; M., Anuradha (International Journal of Basic & Clinical Pharmacology, 2019)
Oxaliplatin is a third-generation platinum derivative used as a first-line agent in the treatment of colorectal carcinoma, biliary tract cancer and gastric cancers and can be used as a neoadjuvant/adjuvant in these cancers. The dose limiting toxicity is peripheral neuropathy, others include hypersensitivity reactions, haematological toxicity and pulmonary fibrosis. Hypersensitivity reactions can extend from milder reactions like urticaria, rash to severe symptoms like hypotension and laryngospasm. The laryngospasm due to oxaliplatin is reported to be reversible with corticosteroids, antihistamines and oxygen. This case series suggest that oxaliplatin has a propensity to cause severe hypersensitivity reaction presenting as laryngospasm not with a single dose but with subsequent doses of oxaliplatin. Prompt symptomatic treatment with corticosteroids leads to reversal of symptoms and improvement in the condition of the patient.